Assessing Junior High School Students’ Numeracy Literacy in Solving Statistical Problems: A Case Study in Sumedang Regency - Siti Sundari; Lia Yuliawati; Neneng Tita Rosita; M. Nuur'aini Sholihat (MASI Mandiri Edukasi, 2025)
This study aims to determine the numeracy literacy level of 8th-grade students at SMP Negeri 9 Sumedang, considering the ongoing challenges in students' ability to interpret, analyze, and solve statistical problems. Many students struggle with numeracy literacy, affecting their ability to make data-driven decisions, which influences their academic achievement, financial literacy, and future employability. This research employs a descriptive qualitative method involving 31 eighth-grade students selected through purposive sampling. Data collection includes students’ numeracy literacy test results on statistical material, interviews, and document analysis. Data analysis follows three stages: data reduction, presentation, and verification. The results indicate that students’ numeracy literacy remains low, with an average test score of 29.3, and only 16% meet the minimum competency level in statistical reasoning. Interviews with two representative students revealed significant difficulties in understanding statistical concepts, particularly in interpreting data from tables and graphs, identifying relevant information for problem-solving, and applying appropriate mathematical strategies. Additionally, students struggled with structuring solutions systematically and drawing meaningful conclusions from statistical data. The primary factors contributing to this low performance include (1) students’ reluctance to engage with lengthy word problems, (2) lack of understanding of prerequisite materials, and (3) difficulties in determining problem-solving strategies. These findings highlight the need for improved instructional strategies to enhance students' statistical reasoning and numeracy literacy. Future research should explore intervention programs that strengthen students’ ability to interpret and apply statistical data in real-world contexts. These findings can help educators design more effective teaching strategies and assist policymakers in developing numeracy-focused curricula that better prepare students for future challenges.